Simulator Design of Kartini Reactor Based on LabVIEW - Sinta Uri El Hakim (BATAN, 2018)
Kartini's Reactor simulator design based on LABVIEW. Kartini’s reactor simulator design has been done to provide a system that can be used as a traning hardware for reactor operator by applying PLC Siemens S7 as a control modul and LabVIEW software as a data processor. The purpose of this research is to design a simulator system to operate Kartini’s Reactor based on reactor kinetics modeling using PLC Siemens S7 as a CRDM controller. LabVIEW software is use as data acquisition and data information processing using reactor kinetics formula to convert the change of height position of control Rod into power information. Control Rod position that obtained from CRDM control will be sent to PC and being processed by software to obtain power. Power that obtained from simulation at 100 kW operation are 100% safety Rod, 60% SHIM Rod, and 37.05% regulator Rod.